The interactive synchronous digital portfolio - Tipán Renjifo, Diego Marcelo (2021)
This research deals with the interactive synchronous digital portfolio as an innovative methodological strategy in the network society, strengthening the self-assessment culture and achieving a high degree of learning and interactivity during synchronous virtual sessions. In the synchronous teaching-learning moments, learning is promoted in the form of a teacher’s monologue through video conferencing, not allowing the students’ participation, construction, and interactivity of learning. The interactive synchronous digital portfolio is proposed as an alternative. According to the results, this innovative methodological strategy can be applied in videoconferences, strengthening the processes of self-evaluation, criticality, metacognition, creativity, continuous participation, and interactivity during virtual classes.